Solution to Shorten Track Usable Length at City Railway Turnout Stations by Using Continuation Routes - SONG Rui (Chengshi guidao jiaotong yanjiu)
［Objective］Compared to the CBTC (communication-based train control) system, CTCS2+ATO (Chinese train control system level 2 + automatic train operation) system requires longer usable track lengths due to its built-in protection zones, leading to increased construction investment for some underground turnout stations. Since city railways tend to have more underground stations, using the CTCS2+ATO system can significantly raise civil engineering costs. To improve the economic efficiency of such projects, it is necessary to study a solution is needed to reduce the track usable length requirements for city railway turnout stations using the CTCS2+ATO system. ［Method］While maintaining the same safety protection distance, it is proposed to use virtual ground data to ensure accurate stopping positions and setting up continuation routes to shorten the effective track length at turnout stations. Key considerations for this solution, such as unlocking methods for continuation routes, signal placement, principles for configuring virtual data, safety guarantees during fault scenarios, and the setup of safety lines, are thoroughly analyzed. ［Result & Conclusion］For unlocking continuation routes, a ′stop and unlock′ method is recommended. At turnout stations with side tracks, it is suggested to install safety lines in the track forward direction instead of the reverse direction to improve the operational efficiency. For city railway turnout stations, the proposed continuation route solution can reduce the distance between the platform end and the basic track joint in front of the turnout from 70 m to 25 m. This can significantly reduce the scale of underground stations, lower civil engineering costs, and improve the project overall economic efficiency.